The Development of Icelandic Foreign Policy: From National Interest to Idealism - Guðjón Örn Sigurðsson 1983- (2012)
This dissertation will look at how Icelandic foreign policy has evolved. With the Union Treaty in 1918 Iceland had declared perpetual neutrality. German aggression in the Second World War and British occupation of Iceland showed that in time of conflict the neutrality policy was unrealistic. Iceland´s strategic position in the Cold War meant that it was forced to bandwagon with the Western camp and entrust the US for its defenses. When European integration started Iceland showed little or no interest as membership would have had little or no economic benefits for Iceland. National interest dominated Icelandic foreign policy during the Cold War epoch and Iceland showed little interest in actively participating in international institutions unless it had direct economic or material benefits. Iceland was far more interested in expanding its fisheries limits and to secure markets for its marine products. This has been cited as the main reason for Iceland´s decision to join EFTA in 1970 and in becoming a member of the EEA agreement. Still the political discourse in the country when the EEA agreement was discussed was mainly fixated on the transfer of sovereignty that the EEA agreement entailed. The Icelandic independence struggle is believed to play an important role and to have had a great impact on the foreign policy approach of Iceland.